First-line Systemic Therapy Following Adjuvant Immunotherapy in Renal Cell Carcinoma: An International Multicenter Study - El Zarif, Talal; Semaan, Karl; Xie, Wanling; Eid, Marc; Zarba, Martin; Issa, Wadih; Zhang, Tian; Nguyen, Charles B; Alva, Ajjai; Fahey, Catherine C; Beckermann, Kathryn E; Karam, Jose A; et al. (European urology, 2024)
BACKGROUND AND OBJECTIVE: Adjuvant pembrolizumab significantly improved overall survival (OS) in renal cell carcinoma (RCC), but real-world data on sequential treatment are scarce. We sought to evaluate the clinical outcomes of first-line (1L) systemic therapy following adjuvant immune oncology (IO)-based regimens. METHODS: A retrospective study including patients with recurrent RCC following adjuvant IO across 29 international institutions was conducted. The primary endpoint was progression-free survival (PFS) on 1L systemic therapy estimated using the Kaplan-Meier method. Preplanned subanalyses of clinical outcomes by type of 1L systemic therapy, recurrence timing, and International Metastatic RCC Database Consortium (IMDC) risk groups were performed. Treatment-related adverse events leading to treatment discontinuation, dose reduction, or corticosteroid use were assessed. KEY FINDINGS AND LIMITATIONS: A total of 94 patients were included. Most received adjuvant pembrolizumab (n = 37, 39%), atezolizumab (n = 28, 30%), or nivolumab + ipilimumab (n = 15, 16%). The cohort included 49 (52%) patients who had recurrence within 3 mo of the last adjuvant IO dose, whereas 45 (48%) recurred beyond 3 mo. Bone metastases were significantly higher in tumors recurring at <3 mo (10/49, 20%) than those recurring at >3 mo (1/45, 2.2%; p = 0.008). Most patients received 1L vascular endothelial growth factor-targeted therapy (VEGF-TT; n = 37, 39%), IO + VEGF-TT (n = 26, 28%), or IO + IO (n = 12, 13%). The remaining underwent local therapy. The median follow-up for the 1L systemic therapy cohort was 15 mo. The 18-mo PFS and OS rates were 45% (95% confidence interval [CI]: 34-60) and 85% (95% CI: 75-95), respectively. Treatment-related adverse events occurred in 32 (42%) patients and included skin toxicity (n = 7, 9.2%), fatigue (n = 6, 7.9%), and diarrhea/colitis (n = 4, 5.3%). Limitations included selecting patients from large academic centers and the short follow-up period. CONCLUSIONS AND CLINICAL IMPLICATIONS: A subset of patients with recurrent RCC following adjuvant IO respond to systemic therapies, including VEGF-TT and IO-based regimens. Notably, patients with favorable-risk disease may derive more benefit from VEGF-TT than from IO therapies in this setting. Future approaches utilizing radiographic tools and biomarker-based liquid biopsies are warranted to detect occult metastatic disease and identify candidate patients for adjuvant IO therapy. PATIENT SUMMARY: Adjuvant pembrolizumab significantly improved overall survival in renal cell carcinoma (RCC). There are limited data on clinical outcomes after the recurrence of RCC tumors following adjuvant immunotherapy. In this study, we find that patients respond to subsequent systemic therapies across different treatment options.
Keywords: protinádorové látky imunologicky aktivní; nádory ledvin; retrospektivní studie; Humans; Carcinoma, Renal Cell; lidé středního věku; Kidney Neoplasms; lokální recidiva nádoru; Middle Aged; karcinom z renálních buněk; Chemotherapy, Adjuvant; Antineoplastic Agents, Immunological; mužské pohlaví; Neoplasm Recurrence, Local; Progression-Free Survival; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; výsledek terapie; Treatment Outcome; imunoterapie; ženské pohlaví; doba přežití bez progrese choroby; lidé; adjuvantní chemoterapie; Aged; senioři; Male; Retrospective Studies; Immunotherapy; Female